Double C-Loop Haptic Lenses Are Rotationally Stable – A Systematic Review - Daya S; Chassain C; Pagnoulle C (Clinical Ophthalmology)
Sheraz Daya,1 Christophe Chassain,2 Christophe Pagnoulle3 1Centre for Sight, East Grinstead, West Sussex, UK; 2Clinique Beau Soleil, Montpellier, France; 3Research and Development Department, BVI, Liège, BelgiumCorrespondence: Christophe Pagnoulle, Research and Development Department, BVI.All. des Noisetiers 4, Liège, 4031, Belgium, Email cpagnoulle@bvimedical.comAbstract: The purpose of this review is to summarize the clinical rotational stability outcomes reported in patients following implantation of the POD platform with double C-loop haptics. A literature search in PubMed (US National Library of Medicine) was carried out to find publications, both prospective and retrospective, which report rotational stability outcomes in patients who were implanted with this platform after cataract or refractive lens exchange surgeries. This platform is used in different commercially available intraocular lenses (IOLs), both monofocal and trifocal, made of hydrophilic or hydrophobic material. 19 clinical peer-reviewed studies published between 2013 and 2024 were included in this review. The data reported in the clinical publications was analyzed in detail, focusing on rotational stability (mean rotation values and ranges, and percentage of eyes with some degrees of rotation), measurement methods and rotation follow-up period. Our review encompassed a total of 1428 eyes implanted with the POD platform analyzed at different follow-up periods, up to a maximum of 26 months. The mean rotation across all the studies was 2.61 °.The analysis carried out in this review leads us to conclude that the POD platform provides good rotational stability when used with different IOL models based on monofocal or trifocal designs and made using hydrophilic or hydrophobic material.Keywords: rotational stability, haptic, double C-loop, intraocular lens, platform